2012
DOI: 10.1182/blood.v120.21.1817.1817
|View full text |Cite
|
Sign up to set email alerts
|

Usage of HLC-Ratio, FLC-Ratio, Ife, PBMC Infiltration and Isotype Suppression At Best Response Reveals Isotype Suppression As Most Powerful Parameter for Identification of Multiple Myeloma Patients with Long Survival

Abstract: 1817 Introduction: Identifying patients with optimal response and long survival is important for clinical guidance because patients with these features are likely not to need further therapy. The techniques applied for classifying these patients should be readily available, standardized, and not liable to subjective interpretation. Here we compare the clinical usability of Hevylite™ (HLC) assay, FLC assay, IFE (immunofixation electropheresis), PMPC (bone marr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…The HLC ratio reflects the balance between monoclonal and polyclonal immunoglobulins of involved and uninvolved isotypes taking into account the polyclonal plasma cell suppression or expansion that occurs with the treatment. However, only few studies have shown the ability of the Hevylite assay to give additional prognostic information in MGUS and MM [ 38 ]. In general, the assay does not add any value to immunofixation or sFLC tests, although it could have some advantages in monitoring patients with M component migrating in β regions [ 39 ].…”
Section: Methodologies For Assessing Minimal Residual Disease In Mmentioning
confidence: 99%
“…The HLC ratio reflects the balance between monoclonal and polyclonal immunoglobulins of involved and uninvolved isotypes taking into account the polyclonal plasma cell suppression or expansion that occurs with the treatment. However, only few studies have shown the ability of the Hevylite assay to give additional prognostic information in MGUS and MM [ 38 ]. In general, the assay does not add any value to immunofixation or sFLC tests, although it could have some advantages in monitoring patients with M component migrating in β regions [ 39 ].…”
Section: Methodologies For Assessing Minimal Residual Disease In Mmentioning
confidence: 99%
“…To overcome some possibilities of error, researchers accredited heavy/light chain (HLC) assay (Hevylite -Binding Site, Birmingham, UK), pairing heavy and light myeloma chains with undiseased ones to undoubtedly define clonal residue (e.g. in patients with IgG-k MM, measuring IgGλ, IgA-k and IgAλ), but the small number of works on the Hevylite method has not yet allowed definition of its potential in terms of prognosis Ludwig, Durie, et al, 2012;Ludwig, Slavka, et al, 2012;Ludwig, Milosavljevic, et al, 2013;Ludwig, Viterbo, et al, 2013;Tovar et al, 2012). Furthermore, in infection or rheumatological disease, determination of the FLC should not be performed, because of its expression of regained jurisdiction of the immune system, which occurs in the healed disease; also in patients with renal impairment, in which FLC ratio is altered due to slower renal clearance of λ-light chain for its dimeric structure, and double production rate of κ-light chain, their use is limited (Hutchison et al, 2008).…”
Section: Serological Response Evaluation By Sflcmentioning
confidence: 99%